Comparison of efficacy and safety of various management options for large upper ureteric stones a systematic review and network meta-analysis - Gopal Sharma (Nature Portfolio, 2021)
Abstract To compare the safety and efficacy of various surgical modalities to manage large (> 1 cm) upper ureter stones. Systematic literature search was conducted to include all randomized studies comparing various treatment options for large (> 1 cm) upper ureteric stones. This review included 13 randomized studies with 1871 patients. Laparoscopic ureterolithotomy (LUL) and percutaneous nephrolithotomy (PNL) were superior to ureteroscopy (URS) and shockwave lithotripsy (SWL) for stone-free rates and need for auxiliary treatments. LUL and PNL were equally effective for stone-free rates and the need for auxiliary treatments. According to SUCRA values for stone-free rates and the need for auxiliary treatments, LUL was the best, followed by PNL. For the duration of surgery, there was no significant difference among all the techniques on network analyses, and SWL was the best according to SUCRA values. Length of hospital stay was significantly shorter for URS than LUL and PNL from network analysis, but there was no significant difference for the rest of the comparisons. Overall complications were similar in all the groups. According to the CINeMa approach, the confidence rating ranged from “very low” to “moderate” for various comparisons. LUL followed by PNL is the most efficacious treatment modality for upper ureteric stones compared to SWL and URS in terms of stone-free rates. However, due to the poor quality of included studies, further high-quality randomized studies are needed.